Unveiling the dynamic coupling and driving mechanisms among digital infrastructure, economic resilience and carbon productivity - Jie Huang; Beibei Zheng; Narisu Liu; Xi Chen (PLoS ONE, 2025)
Investigating the coupled and coordinated relationship among digital infrastructure (DI), economic resilience (ER) and carbon productivity (CP) is pivotal for advancing sustainable development in China. This study employs multiple approaches, including the coupling coordination model, kernel density estimation, Markov chain, and spatial Durbin model, to analyze the spatiotemporal evolution and driving factors of the coupling coordination degree (CCD) from 2013 to 2021. The findings are as follows. First, the average levels of DI, ER and CP show a consistent upward trajectory. Second, the CCD among the three systems exhibits steady growth, transitioning from a state of “general out of balance” to “barely coupling coordination”. Spatially, the CCD demonstrates a characteristic pattern of decreasing from east to west. Overall, achieving a “cross-level transition” in CCD is challenging, and the neighboring provinces significantly influence the enhancement of local CCD. Third, the CCD demonstrates a positive spatial agglomeration effect, with stable hotspots concentrated in regions such as Hubei, Anhui, Zhejiang, and Shanghai. Fourth, strategic emerging industries, population density, human capital, and environmental regulation intensity positively contribute to the local CCD, whereas financial development exerts a negative impact. Regarding spatial spillover effects, strategic emerging industries and environmental regulation intensity exert positive influences, while population density shows a negative effect. Meanwhile, the spatial spillover effects of human capital and financial development are not significant.